Governance and social capital in the co-management of benthic resources in Chile: contributions from a network analysis to the study of small-scale artisanal fisheries - Andrés Marín; Stefan Gelcich (CUHSO)
Co-management or collaborative management is considered tobe a relational institution, since it places emphasis not only on the administrationof resources as such, but also on the social relations between multipleactors with diverse interests in the territory. For this reason, growing interestexists in studying comanagement using social network analysis (sna) and therelated concept of social capital. In this article, we present two applicationsfor the use of sna to understand co-management, using the Chilean systemof Management and Exploitation Areas for Benthic Resources (amerb) as acase study. sna tools are applied speci-fically to: 1) describe and analyse thegovernance network underlying the amerb system, and 2) explore the roleof fisher organizations’ social capital in co-management functioning andperformance. Based on the applications described in the article, we proposethe social network approach as a promising and complementary standpointfor the development and reformulation of more effective public policy, withgrowing participation of local communities.